Restoring Islamic Golden Age: 21st Century Bayt al-Hikmah - Akhmetova, Elmira (2017)
This paper discusses the issue of Bayt al-Hikmah in the 21st Century. It focuses on the following questions: 1. Is it possible to have a Bayt al-Hikmah today? 2. If Yes, HOW? In WHAT form? WHERE? Or WHICH Country does deserve to be a place for it?